STRATEGI PENINGKATAN DAYA SAING BERBASIS ANALISIS SWOT (Studi Kasus pada Startup UFO Burger Bojonegoro - Ahmad, Rofaq Azharul; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
UFO Burger Bojonegoro Startup is a fast-food company facing tough competition in the digital era. To stay ahead, it's important to conduct a SWOT analysis, which involves three stages: input (EFE and IFE), matching (SWOT table and Grand Strategy Matrix), and decision-making (QSPM Matrix). The EFE analysis resulted in a total weighted score of 3.46, with an opportunity value of 1.79 and a threat value of 1.67. The IFE analysis resulted in a total weighted score of 3.63, with a strength value of 1.88 and a weakness value of 1.75. The most effective strategy is the SO strategy with a score of 3.67. The Grand Strategy Matrix places the company in quadrant I, indicating intensive integration and diversification strategies. According to the QSPM Matrix, the most suitable strategies for UFO Burger Bojonegoro Startup are Vertical Integration and Conglomerate Diversification.